Confidence building measures in South Asia - Banerjee, Dipankar; Regional Centre for Strategic Studies (Colombo, Sri Lanka) (Colombo : Regional Centre for Strategic Studies, 1999)
Contributed articles presented at a conference.
Keywords: Confidence and security building measures (International relations) -- South Asia -- Congresses; Confidence and security building measures (International relations) -- Congresses